2018
DOI: 10.1039/c8lc00035b
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thrombotic strategies for microfluidic blood processing

Abstract: The redundant mechanisms involved in blood coagulation are crucial for rapid hemostasis. Yet they also create challenges in blood processing in medical devices and lab-on-a-chip systems. In this work, we investigate the effects of both shear stress and hypothermic blood storage on thrombus formation in microfluidic processing. For fresh blood, thrombosis occurs only at high shear, and the glycoprotein IIb/IIIa inhibitor tirofiban is highly effective in preventing thrombus formation. Blood storage generally act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Studies of plasma fibrinogen and platelet integrin α IIb β 3 [32,33] support the above viewpoints, suggesting that under relatively low shear conditions (< 1,000 s -1 ), integrin α IIb β 3 on the surface of free-flowing platelets can engage fibrinogen adsorbed onto the surface of the thrombus; in addition, the subsequent stimulation of platelets by locally generated soluble agonists induces a platelet shape change and an increase in integrin α IIb β 3 affinity, which helps stabilize and sustain integrin α IIb β3-fibrinogen bonds. Studies on plasma vWF [25,27,31] also showed that, at a low shear of < 30 dyn•cm -2 (converted into a shear rate of ~187 s -1 , when considering that the blood viscosity in this model is 1.6 × 10 -2 Pa•s, which is estimated from the empirical relationship for blood flow in tubes with diameters of < 1 mm [34]), vWF remains inactive. When the shear increases beyond 80 dyn•cm -2 (~500 s -1 ), vWF polymerization occurs and begins to induce platelet aggregation; the mechanisms mediated by integrin α IIb β 3 and vWF are not mutually exclusive, and both operate within the intermediate shear range; at an extremely high pathological shear level of > 300 dyn•cm -2 (~1875 s -1 ), the relative contribution of vWF to thrombosis increased significantly and eventually replaced integrin α IIb β 3 as the main mechanism.…”
Section: Mechanism Of Flow-mediated Platelet Accumulation On Microvasmentioning
confidence: 76%
See 2 more Smart Citations
“…Studies of plasma fibrinogen and platelet integrin α IIb β 3 [32,33] support the above viewpoints, suggesting that under relatively low shear conditions (< 1,000 s -1 ), integrin α IIb β 3 on the surface of free-flowing platelets can engage fibrinogen adsorbed onto the surface of the thrombus; in addition, the subsequent stimulation of platelets by locally generated soluble agonists induces a platelet shape change and an increase in integrin α IIb β 3 affinity, which helps stabilize and sustain integrin α IIb β3-fibrinogen bonds. Studies on plasma vWF [25,27,31] also showed that, at a low shear of < 30 dyn•cm -2 (converted into a shear rate of ~187 s -1 , when considering that the blood viscosity in this model is 1.6 × 10 -2 Pa•s, which is estimated from the empirical relationship for blood flow in tubes with diameters of < 1 mm [34]), vWF remains inactive. When the shear increases beyond 80 dyn•cm -2 (~500 s -1 ), vWF polymerization occurs and begins to induce platelet aggregation; the mechanisms mediated by integrin α IIb β 3 and vWF are not mutually exclusive, and both operate within the intermediate shear range; at an extremely high pathological shear level of > 300 dyn•cm -2 (~1875 s -1 ), the relative contribution of vWF to thrombosis increased significantly and eventually replaced integrin α IIb β 3 as the main mechanism.…”
Section: Mechanism Of Flow-mediated Platelet Accumulation On Microvasmentioning
confidence: 76%
“…Fluorescently label: platelets (green) and fibrin (ogen) (red), respectively. vWF activity by interfering with disulfide bonding, thereby preventing vWF-mediated thrombosis [31]. As shown in Figs.…”
Section: Hemostasis Under Altered Microenvironmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though CTC-iChip could process 10 mL of blood per hour, the very narrow microchannels of its 128 parallel DLD arrays limited scalability to larger blood volumes and incurred loss of CTCs as small as the lower half of WBCs. DLDs also suffer from shear-induced clogging ( Loutherback et al., 2012 ; Wong et al., 2018 ) made worse by prolonged contact of blood with tiny posts in narrow channels. Since the original DLD-based CTC-iChip , blood throughput has been raised by replacing the DLD debulking modules with an array-format inertial focusing device, as described in ( Mutlu et al., 2017 ).…”
Section: Enrichment By Antigens Specific To Ctcs or Wbcsmentioning
confidence: 99%
“…More recently, deterministic lateral displacement (DLD) was used to isolate CTCCs 16 . DLDs require channels near in size to sorted cells to ensure bumping across streamlines and thus struggle to process large blood volumes without clogging 21 (platelettargeted additives can aid processing 22 ).…”
Section: Introductionmentioning
confidence: 99%